Factors Related to Pump Thrombosis With the Heartmate II Left Ventricular Assist Device. Issue 10 (18th August 2015) - Klodell, Charles T.; Massey, H. Todd; Adamson, Robert M.; Dean, David A.; Horstmanshof, Douglas A.; Ransom, John M.; Salerno, Christopher T.; Cowger, Jennifer A.; Aranda, Juan M.; Chen, Leway; Long, James W.; Dembitsky, Walter
ABSTRACT Background Recent reports suggested that HeartMate II (HMII) thrombosis rates may be higher in implants after 2011. We characterize events at HMII centers (>100 HMII implants) whose device thrombosis rates are equivalent or lower than reported by INTERMACS. Methods Seven centers pooled implants from 2011 through June 2013 to examine pump thrombus and identify characteristics and clinical strategies that potentially mitigate the risk. A total of 666 patients (age 59 ± 13 years; 81% male) were studied (support duration: 13.7 ± 8.3 months, cumulative: 759 patient years). Median target INR was 2.25 (range 2.0 to 2.5), and median pump speed was 9200 rpm (range 8600 to 9600). Pump thrombus was suspected with clinical evidence (e.g., hemolysis, positive ramp test) requiring intervention (e.g., anticoagulation therapy, pump exchange) or patient death. Results Suspected pump thrombus occurred in 24/666 (3.6%) patients within three months of implant. At six months, 38/666 (5.7%) had suspected pump thrombus including 24 (3.6%) resulting in pump exchange or death. Stroke (hemorrhagic: 0.049, and ischemic: 0.048 events/patient year) and survival (six months: 88 ± 1%; 1 year: 81 ± 2%) were consistent with national averages. Suspected pump thrombus patients were younger (55 ± 13 vs. 59 ± 13, p = 0.046) and had more females (31.6% vs. 18.3%, p = 0.054). There was no difference in indication, etiology of heart failure, or body size. Conclusions This analysis demonstrates low HMII thrombus events. Minimization of risk factors by uniform implant techniques and consistent post‐op management may reduce device thrombosis. A larger scale multicenter evaluation may better elucidate the difference in thrombus events between centers. doi: 10.1111/jocs.12607 (J Card Surg 2015;30:775–780)